Missionary Methods St Paul's or Ours? - Allen, Roland (Havertown : Lutterworth Press, 2012)
Within a decade, St. Paul established the Church in the four provinces of Galatia, Macedonia, Achaia and Asia. This informative study focuses on the social background to the Apostle's missionary journeys with comparisons between his methods and those of the modern day. The book divides into five parts; the first examines the social and religious world which the Apostle inhabited in AD 50; the second addresses how St. Paul presented the Christian Gospel and his financial policy of self-support for the new churches. Here, contrasts are made between St. Paul's financial and missionary principles
Chapter 9: The Training of Candidates for Baptism and OrdinationPart IV: St Paul's Method of Dealing with Organized Churches; Chapter 10: Authority and Discipline; Chapter 11: Unity; Part V: Conclusions; Chapter 12: Principles and Spirit; Chapter 13: Application; Chapter 14: Epilogue: A Present-day Contrast ; Back Cover.
Print version record.
Master record variable field(s) change: 072
Keywords: Paul, -- the Apostle, Saint; Paul, -- the Apostle, Saint; Missions; RELIGION -- Christian Ministry -- Missions; Missions; RELIGION / Christian Ministry / Missions; Electronic books